Implementation of the Preference Selection Index (PSI) Method in Employee Performance Assessment of PT Mawarindo - Try Setia Budi; Maryaningsih Maryaningsih; Abdussalam Al Akbar (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
PT. Mawarindo Bengkulu City is one of the universities engaged in advertising (Advertising, Baleho and Banners), which so far have not used an evaluation system in objective performance appraisals, employee assessments are carried out based on subjective assessments and do not use indicators capable of providing an assessment. objective on employee performance. So the Preference Selection Index (PSI) method of performance assessment is needed, which will be applied to PT. Mawarindo Bengkulu City. For that the author tries to build an application with the Preference Selection Index (PSI) method on employee performance appraisal using Visual Basic Net, in order to facilitate PT. Mawarindo in the selection of the best employees every year. Based on the results of the study, the Implementation of the Preference Selection Index (PSI) method in assessing the performance of employees of PT. Mawarindo is made using Visual Basic Net programming language with SQL server database as supporting media, storing the results of data processing that can be used by PT. Mawarindo in inputting employee data, so that it can help overcome existing problems so that the process of selecting the best employees at PT. Mawarindo can be done using an application that has been designed.